The Impact Of Loneliness On The Intensity Of Mobile Phone Use Among Early Adolescents Of The Gen-Alpha Generation - Erni Erni; Hotpascaman Simbolon (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to analyze the Impact of Loneliness on the Intensity of Mobile Phone Use in Early Adolescents of the Gen-Alpha Generation. The subjects in this study were early adolescents of the Gen-Alpha generation. Early adolescents in this study are defined as individuals aged 12-14 years, according to the developmental age limits. Based on the results of the research that has been carried out, the following conclusions can be drawn: There is a significant relationship between loneliness and the intensity of mobile phone use. This result is proven by the value of the loneliness variable on the intensity of mobile phone use variable of .000, namely .000 > 0.05. This shows that the research hypothesis is accepted, namely there is an impact of loneliness on the intensity of mobile phone use in early adolescents of the Gen-Alpha generation. The Pearson Correlation value of = .948 indicates a positive direction of the relationship between loneliness and the intensity of mobile phone use. This shows that the loneliness variable (X) has a strong level of relationship with the intensity of mobile phone use variable (Y), namely a unidirectional relationship. If the X variable increases then the Y variable also increases